Dryophthorinae (Coleoptera: Curculionidae) in the Collection of the Museu Paraense Emílio Goeldi: inventory and type specimens - Valente, Roberta de Melo; Guimarães, José Raimundo Rocha (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2021)
This paper reports the results of the curation of specimens of Dryophthorinae (Coleoptera: Curculionidae) housed in the Entomological Collection of the Museu Paraense Emílio Goeldi (MPEG), Belém, state of Pará, Brazil. The Collection holds a total of 1,071 specimens, with 90% of them previously unidentified. We reviewed all specimens and identified them to species level, resulting in 16 genera and 32 species of Dryophthorinae. These include the type specimens of three species: Cyrtomasius marluciae Vanin, 1998; Foveolus maculatus O’Brien, 2003; and Paramasius cristulatus Vanin, 1998. The genus Rhodobaenus Le Conte, 1876 was recorded for the first time to Brazilian Amazon. All specimen data were digitized and are now publicly available. Currently, 50% of the richness of the Dryophthorinae recorded from Brazilian Amazon is present in the Collection. The occurrence and the species richness of the Dryophthorinae examined are shown on a map. All labels contents and remarks to type material are presented. High resolution photographs of the primary types are also provided. The material examined represents a temporal and spatial record of Amazonian Dryophthorinae.